One new and four newly recorded species of the genus Macrobrachium (Decapoda: Caridea: Palaemoindae) from Guangdong Province, southern China - Guo, Zhao-Liang; He, Shun-Lian (Zootaxa, 2008)
The present study, based on a faunistic and ecological survey of the genus Macrobrachium from Guangdong Province, expands the knowledge of morphology, coloration, and distribution of an undescribed species and four new records for M. formosense Bate, 1868, M. inflatum Liang & Yan, 1985, M. maculatum Liang & Yan, 1980 and M. meridionalis Liang & Yan, 1983. A more complete diagnosis of these five species is presented. Macrobrachium heterorhynchos, new species, can be distinguished from its congeners by a combination of characters which includes rostral sexual dimorphism, the two teeth at the proximal part of the cutting edge of the fixed finger of the second pereiopod, the non-inflated palm, and the distinctly longer merus compared which is distinctly longer than the palm or the ischium.